Dynamic Behavior of Microtubules during Dynein-dependent Nuclear Migrations of Meiotic Prophase in Fission Yeast - Yamamoto, Ayumu (The American Society for Cell Biology, 2001)
During meiotic prophase in fission yeast, the nucleus migrates back and forth between the two ends of the cell, led by the spindle pole body (SPB). This nuclear oscillation is dependent on astral microtubules radiating from the SPB and a microtubule motor, cytoplasmic dynein. Here we have examined the dynamic behavior of astral microtubules labeled with the green fluorescent protein during meiotic prophase with the use of optical sectioning microscopy. During nuclear migrations, the SPB mostly follows the microtubules that extend toward the cell cortex. SPB migrations start when these microtubules interact with the cortex and stop when they disappear, suggesting that these microtubules drive nuclear migrations. The microtubules that are followed by the SPB often slide along the cortex and are shortened by disassembly at their ends proximal to the cortex. In dynein-mutant cells, where nuclear oscillations are absent, the SPB never migrates by following microtubules, and microtubule assembly/disassembly dynamics is significantly altered. Based on these observations, together with the frequent accumulation of dynein at a cortical site where the directing microtubules interact, we propose a model in which dynein drives nuclear oscillation by mediating cortical microtubule interactions and regulating the dynamics of microtubule disassembly at the cortex.